Rehabilitation of children with post-burn scars of the distal limbs - O.V. Filippova; K.A. Afonichev (LCC «Medicine-Inform», 2021)
O.V. Filippova, K.A. Afonichev G.I. Turner National Medical Research Center for Сhildren's Orthopedics and Trauma Surgery, Pushkin, St. Petersburg, Russian Federation Background: rehabilitation after burns of the distal limbs is a challenging process due to many small joints and heavy functional load. During active growth periods, the risk of rapid progression of deformities is particularly high as intensive growth under scarring may result in sprains and even bone angulation. Regular monitoring is a prerequisite for adequate treatment. Aim: to analyze the rate and terms of the development of foot deformities in children of various ages and the actual amount of rehabilitation measures based on clinical anamnestic data. Patients and Methods: anamnestic data, clinical presentations, and X-ray exams of 65 children with foot deformities who were managed in the G.I. Turner National Medical Research Center for Children's Orthopedics and Trauma Surgery in 2015-2019 were analyzed. All children were distributed across age groups. Results: the analysis of anamnestic data revealed an inadequate amount of preventive rehabilitation measures after skin integrity recovery. In half of the patients, conservative therapy included anti-scarring creams and gels and, occasionally, compression clothing. The highest rate of scar deformities requiring surgery was reported in preschool and early school children (these are the ages of rapid growth). In preschool children, scar deformities are significantly m ore common in the earliest period (up to 2 years after epithelization). Conclusion: rehabilitation of children after burns should be continued until a child stops growing. These measures should include complementary surgical and conservative treatment in both in-patient and out-patient departments. Keywords: burn, scar deformities, foot deformities, check-up of children after burns, prevention of scarring. For citation: Filippova O.V., Afonichev K.A. Rehabilitation of children with post-burn scars of the distal limbs. Russian Journal of Woman and Child Health. 2021;4(2):168-172. DOI: 10.32364/2618-8430-2021-4-2-168-172.